2019
DOI: 10.1093/ckj/sfz096
|View full text |Cite
|
Sign up to set email alerts
|

Home run—results of a chronic kidney disease Telemedicine Patient Education Study

Abstract: Background Chronic kidney disease (CKD) incidence is increasing and associated mortality and morbidity are high. Educating patients is effective in delaying progression and establishing optimal renal replacement therapy (RRT). Tele-education/telemedicine (TM) can be an effective tool to provide such education, but there are no available data quantifying its effectiveness. We attempted to establish such evidence correlating the effect of education in patient choices and with the start of actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 13 publications
0
37
2
Order By: Relevance
“…The Zuni telenephrology clinic delivered pre-ESKD education along with pre-ESKD care to patients living in rural areas (6). Another trial of dialysis modality education via telemedicine revealed remarkable success, where 90% of patients were able to make an informed decision and home modality choices doubled (9). At UAB, during COVID-19, CKD education and dialysis modality classes have been conducted successfully via a virtual format twice a month.…”
Section: Telenephrology Education Strategiesmentioning
confidence: 99%
“…The Zuni telenephrology clinic delivered pre-ESKD education along with pre-ESKD care to patients living in rural areas (6). Another trial of dialysis modality education via telemedicine revealed remarkable success, where 90% of patients were able to make an informed decision and home modality choices doubled (9). At UAB, during COVID-19, CKD education and dialysis modality classes have been conducted successfully via a virtual format twice a month.…”
Section: Telenephrology Education Strategiesmentioning
confidence: 99%
“…[17][18][19] CKD awareness is assessed by the prior validated instrument by Wright et al [20] Considering this and other similar validated CKD knowledge instruments lack the domains of ESKD knowledge-essential for informed dialysis decision-the team has developed and pilot tested a 29-item ESKD knowledge questionnaire. [21] This questionnaire will be further re ned during the TEACH-VET, and the team will report on its ndings. A full list and timeline of all collected variables are listed in Figure 1 and Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have shown the advantages of such two-phase approach on comprehension, fears, and home dialysis selection. [26,21] Over last decade, we have tested, re ned and validated this protocol at two geographically distinct universities and a liated VAs within the US to ensure literacy level and cultural relevance for the target patient population. [11,12] For this study, we further pilot-tested the intervention with a local Veteran Engagement Committee made up of a diverse group of 12 Veterans and Veteran caregiver volunteers from Florida.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There seems to be ample demand for home dialysis if patients are educated about the therapy. Comprehensive predialysis tele-education may increase home dialysis adoption; tele-education can be scaled to size with limited marginal cost (6). In transitional care units, which are emerging across the country, patients are educated during multiple weeks of in-center HD about all dialytic modalities as well as kidney transplantation.…”
mentioning
confidence: 99%